Short Communication: Morpho-agronomic performances of bird pepper (Capsicum annuum) lines under varying agro-ecological locations in Indonesia - MUHAMAD SYUKUR; ZULFIKAR DAMARALAM SAHID; SOBIR SOBIR; AWANG MAHARIJAYA; ARYA WIDURA RITONGA; SULASSIH SULASSIH; MUHAMMAD RIDHA ALFARABI ISTIQLAL; ABDUL HAKIM; ARYA YUDA PANGESTU; UNDANG UNDANG; TIARA YUDILASTARI; DWIKA SYATTWA ARANDITO; SYAFIK ASHAR; AGHNIYA’UL HASANAH; KARLIN AGUSTINA; RULI JOKO PURWANTO; KARYANI KARYANI; MARLINA MUSTAFA; YOLANDA FITRIA SYAHRI; CITRA RAMLASARI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Syukur M, Sahid ZD, Sobir, Maharijaya A, Ritonga AW, Sulassih, Istiqlal MRA, Hakim A, Pangestu AY, Undang, Yudilastari T, Arandito DS, Ashar S, Hasanah A, Agustina K, Purwanto RJ, Karyani, Mustafa M, Syahri YF, Ramlasari C. 2022. Short Communication: Morpho-agronomic performances of bird pepper (Capsicum annuum) lines under varying agro-ecological locations in Indonesia. Biodiversitas 23: 4838-4843. Bird pepper price fluctuations are caused by an imbalance between production and market demand. One effective way to overcome this is to increase the productivity of bird pepper. Genetics and the growing environment of bird pepper greatly affect the productivity produced. Therefore, this study aimed to determine the character of yield and yield components of four genotypes of bird pepper at three lowland locations. Planting was carried out at three locations representing Indonesia's bird pepper growing environment. The planting procedure in all sites was carried out according to the same guidelines. A randomized complete block design (RCBD) was used with three replications. Twenty (20) plants per genotype were planted in each replicate, with 10 plants taken as samples. Shiara IPB had the highest productivity in all environments compared to the other line. The main characteristics that distinguish this variety had a purplish color on the fruit petals when young, and the fruit color was greenish-yellow. Hierarchical cluster analysis results showed that Shiara IPB in almost all observation variables based on legend color was superior. The highest productivity was found in Palembang, followed by Bogor and Kolaka.